The changes in running performance and maximal oxygen uptake after long-term training in elite athletes - Legaz Arrese, A.; Serrano Ostariz, E.; Jcasajus Mallen, J. A.; Munguia Izquierdo, D. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The relationship between V.O2max (mL·kg-1·min-1) and running performance has been assessed in cross-sectional studies. Follow-up studies of the long-term effects of running training on the changes in performance and V.O2max have not been undertaken. Methods: Twenty-five male endurance-trained (MET) and 8 female endurance-trained (FET) athletes were tracked over 4 years. In each event the athletes were divided into Class A, including half the number of athletes with the best performances, and Class B. V.O2max, examined at the end of the competitive season, and the best performance was chosen each year. Results: After 3 years of training, in MET and FET athletes the performance improved by 1.77% and 0.69% (P<0.01 and P=0.579), respectively. In Class A runners, training resulted in non-significant increase in performance (-0.04%) (P=0.982) and in Class B runners, performance increased by 3.16% (P=0.001). In all groups V.O2max remained essentially unchanged. Longitudinal changes in the V.O2max were not related with the changes in running performance in any group. Conclusion: This study show than in older runners with more years of training, heavy training does not produce improvements in running performance neither changes in the V.O2max. It is possible that these elite athletes have reached the plateau in their performance; although unlikely, some improvement in training techniques may happen and break the present limit. In younger runners with less years of training, heavy training produce improvements in running performance without changes in the V.O2max. These athletes that had not attained his biological limits at the beginning of study improved the performance in competition and it is quite probable that this improvement be due to training. The changes in performance were not related to changes in V.O2max. Consequently, another physiological or psychological variables must be studied by longitudinal form to explain the variability of performance in competition.